TI_GERICHTE 12.2014.169 vom 21. März 2016 , Mutuo - restituzione del denaro - errronea informativa sull'importo da restituire - TI Tribunale d'appello (2016)
Mutuo - restituzione del denaro - errronea informativa sull'importo da restituire